Hydrogen storage in Mg-LiBH4 composites catalyzed by FeF3 - Puszkiel, Julián Atilio; Gennari, Fabiana Cristina; Arneodo Larochette, Pierre Paul; Troiani, Horacio Esteban; Karimi, Fahim; Pistidda, Claudio; Gosalawit e Utke, Rapee; Jepsen, Julian; Jensen, Torben R.; Gundlach, Carsten; Tolkiehn, Martin; Bellosta von Colbe, José; et al. (Elsevier Science, 2014)
Fil: Puszkiel, Julián Atilio. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Centre for Materials and Coastal Research; Alemania